(untitled) (Sciences & Technologie. C, Biotechnologies, 2015)
The present study concerned the biomolecular and bioinformatic characterization of psychrotrophic bacteria resistant to cephazolin, in particular Stenotrophomonas spp.The raw milk samples (N = 64) of 30 cows were collected in Biskra, in the South-East of Algeria. All the characteristics tested allowed the presumptive identification of Stenotrophomonas spp. The sequence of the 16S rRNA was used on the BlastN bioinformatics tool of the NCBI portal. The results of the alignment with GenBank 16S RNA sequences confirmed the species: it is Stenotrophomonasmaltophilia.